On a limit theorem for an additive functional on a nonrecurrent Markovian chain - Ruzhevich, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish conditions under which the distribution of an additive functional on a nonrecurrent Markovian chain is asymptotically normal.